Development of a Tissue‐Engineered Lymphatic Graft Using Nanocomposite Polymer for the Treatment of Secondary Lymphedema. Issue 3 (30th October 2015) - Kanapathy, Muholan; Kalaskar, Deepak; Mosahebi, Afshin; Seifalian, Alexander M.
Abstract: Damage of the lymphatic vessels, commonly due to surgical resection for cancer treatment, leads to secondary lymphedema. Tissue engineering approach offers a possible solution to reconstruct this damage with the use of lymphatic graft to re‐establish the lymphatic flow, hence preventing lymphedema. The aim of this study is to develop a tissue‐engineered lymphatic graft using nanocomposite polymer and human dermal lymphatic endothelial cells (HDLECs). A nanocomposite polymer, the polyhedral oligomeric silsequioxane‐poly(carbonate‐urea)urethane (POSS‐PCU), which has enhanced mechanical, chemical, and physical characteristics, was used to develop the lymphatic graft. POSS‐PCU has been used clinically for the world's first synthetic trachea, lacrimal duct, and is currently undergoing clinical trial for coronary artery bypass graft. Two designs and fabrication methods were used to manufacture the conduits. The fabrication method, the mechanical and physical properties, as well as the hydraulic conductivity were tested. This is followed by in vitro cell culture analysis to test the cytocompatibility of HDLEC with the polymer surface. Using the casted extrusion method, the nanocomposite lymphatic graft demonstrates desirable mechanical property and hydraulic conductivity to re‐establish the lymphatic flow. The conduit has high tensile strength (casted: 74.86 ± 5.74 MPa vs. coagulated: 31.33 ± 3.71 MPa; P < 0.001), favorable kink resistance, and excellent suture retention property (casted vs. coagulated, P < 0.05). Cytocompatibility study showed that the POSS‐PCU scaffold supports the attachment and growth of HDLECs. This study demonstrates the feasibility of developing a tissue‐engineered lymphatic graft using the nanocomposite polymer. It displays excellent mechanical property and cytocompatibility to HDLECs, offering much promise for clinical applications and as a new treatment option for secondary lymphedema.